Distinct expression/function of potassium and chloride channels contributes to the diverse volume regulation in cortical astrocytes of GFAP/EGFP mice - Benesova, Jana; Rusnakova, Vendula; Honsa, Pavel; Pivonkova, Helena; Dzamba, David; Kubista, Mikael; Anderova, Miroslava (PloS one, 2012)
Recently, we have identified two astrocytic subpopulations in the cortex of GFAP-EGFP mice, in which the astrocytes are visualized by the enhanced green-fluorescent protein (EGFP) under the control of the human glial fibrillary acidic protein (GFAP) promotor. These astrocytic subpopulations, termed high response- (HR-) and low response- (LR-) astrocytes, differed in the extent of their swelling during oxygen-glucose deprivation (OGD). In the present study we focused on identifying the ion channels or transporters that might underlie the different capabilities of these two astrocytic subpopulations to regulate their volume during OGD. Using three-dimensional confocal morphometry, which enables quantification of the total astrocytic volume, the effects of selected inhibitors of K⁺ and Cl⁻ channels/transporters or glutamate transporters on astrocyte volume changes were determined during 20 minute-OGD in situ. The inhibition of volume regulated anion channels (VRACs) and two-pore domain potassium channels (K(2P)) highlighted their distinct contributions to volume regulation in HR-/LR-astrocytes. While the inhibition of VRACs or K(2P) channels revealed their contribution to the swelling of HR-astrocytes, in LR-astrocytes they were both involved in anion/K⁺ effluxes. Additionally, the inhibition of Na⁺-K⁺-Cl⁻ co-transporters in HR-astrocytes led to a reduction of cell swelling, but it had no effect on LR-astrocyte volume. Moreover, employing real-time single-cell quantitative polymerase chain reaction (PCR), we characterized the expression profiles of EGFP-positive astrocytes with a focus on those ion channels and transporters participating in astrocyte swelling and volume regulation. The PCR data revealed the existence of two astrocytic subpopulations markedly differing in their gene expression levels for inwardly rectifying K⁺ channels (Kir4.1), K(2P) channels (TREK-1 and TWIK-1) and Cl⁻ channels (ClC2). Thus, we propose that the diverse volume changes displayed by cortical astrocytes during OGD mainly result from their distinct expression patterns of ClC2 and K(2P) channels.
Keywords: modulátory membránového transportu; sodík-draslík-chloridové symportéry; Gene Expression Regulation; kotransportéry pro draslík a chloridy; draslíkové kanály; Glucose; Male; Oxygen; vezikulární transportní proteiny pro glutamát; Vesicular Glutamate Transport Proteins; Sex Characteristics; chloridové kanály; K Cl- Cotransporters; Astrocytes; techniky in vitro; velikost buňky; mozková kůra; Sodium-Potassium-Chloride Symporters; glukosa; mužské pohlaví; pohlavní dimorfismus; stanovení celkové genové exprese; Models, Biological; Gene Expression Profiling; Potassium Channels; zelené fluorescenční proteiny; Animals; kyslík; lidé; biologické modely; ženské pohlaví; myši transgenní; Symporters; Humans; gliový fibrilární kyselý protein; zvířata; regulace genové exprese; Chloride Channels; Glial Fibrillary Acidic Protein; Green Fluorescent Proteins; myši; Mice, Transgenic; symportéry; astrocyty; Female; Mice; Membrane Transport Modulators; Cell Size; In Vitro Techniques; Cerebral Cortex